PENGARUH METODE LATIHAN TERHADAP KEMAMPUAN PASSING BAWAH BOLA VOLI PADA PESERTA EKSTRAKURIKULER DI SMP NEGERI 1 BERASTAGI TAHUN AJARAN 2025/2026 - Arjuna Barus; Janwar Firhasan Sinuraya; Julius Boy Nesra Basgimata Barus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of underpassing training using a target area on volleyball underpassing skills in extracurricular participants at SMP Negeri 1 Berastagi for the 2025/2026 academic year. This research uses a quantitative approach with experimental methods and One Group Pretest-Posttest Design. The research sample consisted of 16 participants who were determined using saturated samp ling techniques. The data collection technique was carried out through a bottom passing skill test before (pretest) and after (posttest) treatment. Data were analyzed using normality test and paired sample t-test hypothesis test. The results of the study showed that the average score of participants' bottom passing skills at the pretest was 45 and increased to 60 at the posttest. The results of the hypothesis test show that the significance value is smaller than 0.05 (p < 0.05), so that there is a significant effect of underpassing training using the target area on the volleyball underpassing skills of extracurricular participants at SMP Negeri 1 Berastagi for the 2025/2026 academic year. Thus, down passing drills using the target area are effective for improving participants' volleyball down passing skills.